Characterization of lightning-induced overvoltages in wind farms - Tamer Eliyan; Saad F. Al-Gahtani; Z.M.S. Elbarbary; Fady Wadie (PLoS ONE, 2025)
Wind farms are exposed to various weather hazards, including lightning strikes, which can pose significant risks. However, the impact of different wind farm topologies on the magnitude of lightning-induced overvoltages has not been extensively studied, creating a gap in existing literature. This paper addresses this gap by analyzing the characteristics of lightning-induced overvoltages injected into the grid for various wind farm topologies. The scientific scope of this study is to evaluate the influence of wind farm topology on the severity of different types of lightning-induced overvoltages including positive, negative, and double-peaked lightning strikes, using simulation-based analysis. The topologies tested include radial, single-sided ring (SSR), double-sided ring (DSR), and star topologies. The results demonstrate that radial topology leads to the highest overvoltage injection, while switching to SSR, DSR, or star topologies results in reductions of overvoltage by 11.5% to 51.0%, 39.5% to 66.0%, and 62.3% to 89.0%, respectively. These results support a topology-based risk assessment approach, offering clear guidance for selecting configurations that improve lightning resilience.